Sharing time: new forms of reciprocity in the digital economy. (1st December 2017) - ,; ,
Abstract : The current debate about the sharing economy has rediscovered the importance of reciprocity as a model of exchange. Time banks, traditionally tools for enhancing an underutilised workforce, are developing at the same time as forms of mutualism and reciprocity within defined communities (residents of a neighbourhood or organisational population of a company), and now have a new opportunity for scaling up through the enabling power of new digital technologies. This article analyses the case of a digital time bank using social network analysis in order to investigate whether the sharing economy can be considered a practice of 're-socializing economic exchange'.